Caracterização de revestimento de 410 NiMo utilizando processo de eletrodo revestido - Soares, Marcus Fellipe Pinatto (2017)
The turbine blades of hydroelectric plants are generally composed by martensitic steels, which are characterized by high hardness and resistance. Over time, it occurs detrition which results in pores and cracks that need repairs. These repairs are made by welding process. This work studies the SMAW process and its parameters to make these repairs. The objective is to analyze the weld quality where the deposition material is the ER 410 NiMo, which is special for the welding of martensitic steels, on a sample taken from a hydroelectric turbine blade made by soft martensitic iron CA6NM, analyzing by Penetrating liquid assay, Microhardness Vickers and Optical Microscopy the addition metal, the HAZ (Heated-affected zone) and the base metal.